Evaluasi Kesesuaian Lahan Pengembangan Tanaman Tembakau (Nicotiana tabacum L) Di Lahan Sawah Kota Langsa Dengan Menggunakan Sistem Informasi Geografis (SIG) - Boy Riza Juanda; Iwan Saputra; destiana saputri simbolon (Jurnal Agrotek Lestari, 2025)
Langsa City is one of the areas that has a fairly large expanse of land for agricultural activities for wetland farming. In addition to the leading plantation commodities, the Aceh Province Agriculture and Plantation Service has scheduled to develop tobacco as one of the leading commodities in Langsa City. Tobacco commodity is a new superior commodity developed in Langsa City starting from 2021 in Pondok Kemuning Village, and 2023 in Buket Meutuah Village, East Langsa District. The productivity and quality of the tobacco are still not optimal, because information on the quality and characteristics of the land for the tobacco development plan in Langsa City is still not known for certain. This study uses a survey method with descriptive analysis based on field observations and laboratory analysis. The process of determining land suitability is carried out using spatial operations by utilizing GIS applications. Based on the physical and chemical analysis of the soil at the sample points and the results of the interpretation of remote sensing data, it was found that the actual land suitability results for tobacco plants in the rice fields of Langsa City in SLH 1 and SLH 2 are Class S3-wa, nr, na with each SLH 1 being 951 Ha (90.65%) and SLH 2 with an area of 98 Ha (9.35%). The results of potential land suitability after efforts to improve the limiting factors in SLH 1 and SLH 2 are class S2-wa orup one level from the actual land suitability class.Keywords: Evaluation, Land, Tobacco, Paddy Fields, GIS